Rescue responses during a full moon and Friday 13th. Issue 2 (5th August 2019) - Greatbatch, Ian; Koester, Robert J.; Kleinsmith, Andrea L.
Abstract : Purpose: It is a well held belief that the full moon period and the date Friday 13th has an impact on the number of emergency call outs for emergency services. The purpose of this paper is to critically explore that belief. It also examines the versatility and richness of response records, and demonstrates the effectiveness of combining data sets. Design/methodology/approach: The work takes four varied data sets, from four rescue agencies along with the International Search and Rescue Database and compared the average number of calls on a full moon night, non-full moon and full moon period (the full moon night, the day before and day after). The average number of incidents on Friday 13th was also investigated. It uses a statistical approach to test the difference between "normal" dates and those dates traditionally believed to be busier. Findings: Although there were differences between Friday 13th, full moon nights, full moon periods and "normal" days, the differences were in general extremely small, not significantly significant and in most cases actually dropped during the supposedly unlucky period. The exception to this is a very small increase in the average number of responses during full moons for most data sets, although this was not statistically significant. This paper concludes that there is no evidence in the data for any impact of the full moon upon rescue teams' activities. Research limitations/implications: This research deals with a small set of responses, from the UK only, and addresses an issue that is clearly not the most pressing. However, it does demonstrate evidenced-based management in practice, in that resources have incorrectly been assigned in the past to these dates. Practical implications: This work shows that preconceptions exist within the emergency services and that, without evidence-led management, resources can be allocated on hearsay. This shows that widely available software and techniques can be applied to organisational data and used to make management decisions more appropriate. Social implications: Rescue organisations are almost exclusively charity or public sector organisations, meaning that their budgets are sourced from donations or the tax-payer. Putting to bed misconceptions over resources for certain dates will ultimately benefit society in those terms. Originality/value: There has been very little work on this phenomenon, although some works on A&E department admissions have taken place. This is the only work to date to combine data in this way for this purpose.